Discurso, sociedade e cognição: texto e contexto em anúncios publicitários - Ribeiro, Maria do Carmo Meirelles Reis Branco (2013)
This Thesis is situated on the Critical Discourse Analysis, with the social cognitive and Social Semiotics sheds. Its theme is the relevance of contexts for text organization in multimodal printed advertisements. Cognition, as well as Society and Discourse must be considered as categories in order to accomplish a discourse critical analysis. Discourse is defined by the social roles performed by its participants, their functions and their actions, text is a product of a multimodal semiotics manifestation, originated in a speech macroact. Including Cognition as an analysis category provides a socio-cognitive point of view for discourse and new perspectives for understanding advertisements multimodal texts. This thesis is justified by the fact that high technologies and globalization have changed discourses, mainly for multimodal texts, so that new possibilities of reading such texts must be improved. This research focused advertisements texts published in Brazilian magazines, from 2005 to 2013. The general purpose is to contribute for studies on multimodal texts. The specifics objectives are: 1.to analyze the relation between images/linguistics expressions in producing meaning; 2.to verify argumentative strategies of advertisement speech macro-act;3.to identify advertisement text organization, in order to consider it a text genre; 4. to examinate the relation text/context in meaning production. The results of this search show that:1. images are linked to verbal expressions, producing meaning, and completing its semic area; 2. strategies are a consequence of space, colors resources, as well as inferences that complete the semic area; 3.advertisement is a text genre, defined by the hierarchy of the argumentative sequence, in which are placed narrative, descriptive and dialogue sequences 4. production and interpretation of advertisements texts is linked to cognitive, language, discourse and social contexts. In conclusion, there is a relation between the Cognition category and the Society and Discourse categories